Consumer Motives and Values: An Exploratory Study of Chinese Middle Classes' Luxury Products Consumption - Wu, Xiaofang (2012)
The purpose of this research is to explore the perceptions of the Chinese middle classes’ luxury consumption and motives for purchasing luxury products. Literature has been reviewed in terms of three aspects: the definition of ‘luxury’, consumer motives and cultural value influence. A framework of co-creating five luxury values from Tynan, McKechnie and Chhuon (2009) is focus of the evaluation and applied to examine Chinese middle classes’ motives for luxury consumption. A qualitative research method is used to conduct the in-depth and semi-structured interviews with eight interviewees who are all from Guangdong Province China and matched the definition of China’s middle class from Wang (2010).